Thomas Percival. Discussing the foundation of Medical Ethics - Patuzzo, Sara; Goracci, Giada; Ciliberti, Rosagemma (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the work: In 1803, the English physician Thomas Percival published Medical Ethics, a work destined to become a milestone in the development of modern codes of medical ethics, starting from the first edition of the American Medical Association’s ethical code. Notwithstanding the undeniable influence that this book has exerted upon the codification of the principles of medical ethics, researchers and experts foster different and opposing points of views on its real nature. They question whether Medical Ethics truly belongs to the literary genre of codes of medical ethics or, better yet, to that of medical etiquettes. Methods: This debate is crucial in the field both of medical history and of medical ethics, with regard not only to Percival’s work, but also to the ethical value of the current codes of medical ethics and deontology. Results: The lack of a rigorous philosophical-moral analysis of the current medical codification is reflected in its mere loyalty to the legal regulation, in substantial continuity with the past. However, the constant challenges proposed by the biomedical development, require the need to rethink the traditional conceptual tools of the current codes of medical ethics, with the purpose to achieve new schemes and innovative solutions. Conclusions: On this perspective, when the codes of medical ethics are worked out by physicians, they could be considered as wrongly titled medical etiquettes. This consideration could regard current codes of medical ethics, that remain faithful to tradition and that would more probably be codes of medical etiquette with a wrong title.